2015
DOI: 10.21909/sp.2015.02.689
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Binaural Beats on Working Memory Capacity

Abstract: Abstract:The research explored the effect of binaural beats on working memory capacity (WMC). When the binaural beat beats with the frequency that corresponds to the state of alpha wave range, then it is believed that the overall brain activity changes accordingly. Brainwave activity within the alpha range has been generally correlated with many cognitive functions along with working memory improvement. Therefore, in this study it is assumed that binaural beat corresponding to alpha wave range will enhance sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
2
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 32 publications
5
28
2
9
Order By: Relevance
“…To avoid these kinds of confounding effects and to be able to draw conclusions about the pure nature of the effects of MBs and BBs, the beats in the current study were not accompanied by music. Positive significant results were found in studies using carrier tones with a frequency of respectively 230 and 220.45 Hz, and 240 and 255 Hz (Beauchene et al, 2016;Kraus & Porubanová, 2015). The carrier tones used in the present study were as high as 440 and 480 Hz, and although the BB with a carrier tone around 440 Hz has been shown to be perceived the best (Oster, 1973), these tones might be too high for comfortable listening.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…To avoid these kinds of confounding effects and to be able to draw conclusions about the pure nature of the effects of MBs and BBs, the beats in the current study were not accompanied by music. Positive significant results were found in studies using carrier tones with a frequency of respectively 230 and 220.45 Hz, and 240 and 255 Hz (Beauchene et al, 2016;Kraus & Porubanová, 2015). The carrier tones used in the present study were as high as 440 and 480 Hz, and although the BB with a carrier tone around 440 Hz has been shown to be perceived the best (Oster, 1973), these tones might be too high for comfortable listening.…”
Section: Discussionsupporting
confidence: 42%
“…Other authors, who did find a significant improvement in performance while listening to BBs, presented ABS for a relatively long duration (30 min on three different days, Lane et al, 1998). However, a long stimulation period (20 min, three times a week for three weeks) has been found not to yield significant results (Kennel et al, 2010), while listening to BBs for only 12 min improved cognitive performance (Kraus & Porubanová, 2015). Thus, it seems that the duration of ABS might not be the key factor to improve performance, and other, still unknown factors should be examined.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kennel et al [11] investigated whether binaural beat entrainment could reduce symptoms of ADHD in children and found that whilst the symptoms did not significantly improve, homework problems due to inattention improved during the 3 week study. A more recent study on working memory found that exposure to binaural beats had a positive effect on participants exposed to a frequency in the alpha range of brain activity, showing significant improvement in working memory compared with the control group [12].…”
Section: Introductionmentioning
confidence: 97%
“…Entrainment of gamma oscillations is of specific interest because of the role of gamma oscillations for attention 21 , feature binding 22,23 , memory 24 , and learning 25 . Beneficial effects of BB stimulation have been reported for memory [26][27][28][29] , attention 30 , creativity 31 , anxiety control 32 , modulation of mood states 27,33 , and pain perception 34 .…”
mentioning
confidence: 99%